RELATIONSHIP OF XEROSIS CUTIS WITH PROTEINURIA DEGREES IN CHILDREN WITH NEPHROTIC SYNDROME AT THE HAJI ADAM MALIK HOSPITAL - Ami Utamiati, Sri Wahyuni Purnama & Irma D Roesyanto (International Journal of Research Science and Management, 2020)
Introduction: xerosis cutis is a disorder of the skin surface due to reduced fluid or oil content in the skin that moisture on the surface of the skin layer decreases. Proteinuria is a risk factor for the progression of nephrotic syndrome. Nephrotic syndrome if there is proteinuria (≥40 mg / m2 / hour or protein / creatinine ratio ≥ 200 mg / mL or protein + 3 on urine dipstick test), hypoalbuminemia (<25 g / L) and edema. Objective: To determine the relationship between xerosis cutis and the degree of proteinuria in children with nephrotic syndrome. Subject and Method: This is is a cross-sectional analytic study, involving 50 subject xerosis cutis with nephrotic syndrome patients. Kruskal Wallis test is used to determine the relationship xerosis cutis with proteinuria degree in children with nephrotic syndrome. This study has been approved by the Health Research Ethics Commission of the Faculty of Medicine, Universitas Sumatera Utara/ H. Adam Malik General Hospital Medan. Result: Based on the characteristics of 50 research subjects, the age of all research subjects has a median value of 8 (3-16) years with the most age range at the age of 6-10 years, as many as 26 subjects (52%), male subjects as many as 34 subjects (68 %) and women as many as 16 subjects (32%). The duration of nephrotic syndrome has a median value of 2 (1-7) years. There was a significant skin dryness relationship based on the degree of proteinuria (p = 0.002). Thus it can be concluded that the higher the degree of proteinuria, the higher the level of dryness of the skin and the greater the degree of proteinuria in children with nephrotic syndrome, then indirectly describe the more protein that is wasted through urine. Conclusion: There is a significant xerosis cutis relationship based on the degree of proteinuria (p= 0,002).